2018
DOI: 10.1007/s40152-018-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergy as strategy: learning from La Restinga, Canary Islands

Abstract: Coastal tourism has been supported by the growth of middle-class tourist markets, promoted by governments who view it as an important avenue for economic growth and backed by environmental organisations who regard it as an alternative, more environmentally sustainable livelihood than capture fisheries. How policymakers and households in coastal areas negotiate the challenges and opportunities associated with growing tourism and declining capture fisheries is increasingly important. Drawing on extended ethnogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…It should be noted that fishermen, nowadays, offer their services as boatmen to locals and tourists. Other case studies have shown that fishermen's cooperatives tend to position themselves for or against the implementation of NPAs or tourism developments based on their leading role in decision-making, the strength of their union organization and the level of access and appropriation of resources susceptible to become tourist attributes as well as the type of synergies established between the different stakeholders in relation to the management of the territory [77]. Another possible factor to consider is the role played by drug trafficking in Central America, as it often uses certain extractive activities, including fishing, for money laundering, with major consequences for conservation governance [78].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that fishermen, nowadays, offer their services as boatmen to locals and tourists. Other case studies have shown that fishermen's cooperatives tend to position themselves for or against the implementation of NPAs or tourism developments based on their leading role in decision-making, the strength of their union organization and the level of access and appropriation of resources susceptible to become tourist attributes as well as the type of synergies established between the different stakeholders in relation to the management of the territory [77]. Another possible factor to consider is the role played by drug trafficking in Central America, as it often uses certain extractive activities, including fishing, for money laundering, with major consequences for conservation governance [78].…”
Section: Discussionmentioning
confidence: 99%
“…The case of Punta de la Restinga and Sea of Calms MR is an example of how small-scale fishers may participate in the design and monitoring/management of MPAs' from step zero (Jentoft et al, 2012), thus increasing their governability as well as the MR's role in stakeholder's synergy building and fostering community development (Pascual-Fernández et al, 2018). The Sea of Calms is historically the main fishing area for the small-scale fishers from La Restinga village, and the MR implementation helped protect this sensitive area where small-local-fishing boats can fish year-round (De la Cruz Modino, 2012).…”
Section: Case Of Study Characterizationmentioning
confidence: 99%
“…While it is difficult to argue a priori against any attempt to protect coastal ecosystems, the history of marine conservation suggests the difficulty of anticipating the full range of social, economic, and environmental impacts at the local level. A large body of social scientific literature on marine protected areas indicates the potential for conflict with residents whose livelihoods and cultural resources are directly or indirectly impacted by conservation efforts, and the challenge of devising interventions that operate synergically (McClanahan et al, 2005;Walley, 2010;Jentoft et al, 2012;Pascual-Fernández et al, 2018;Sowman and Sunde, 2018). A recent analysis of "blue carbon" strategies in Tanzania and Mozambique suggests, for example, multiple points of friction with a wide range of subsistence activities-from the reliance on mangrove forests for fuelwood, to small-scale trawling for fish, and crustaceans in seagrass meadows (Gullström et al, 2021; see also Veitayaki et al, 2017).…”
Section: Marine Cdr As Localized Interventionmentioning
confidence: 99%